Use of cefoxitin as indicator for detection of Methicillin Resistant Staphylococcus aureus (Baghdad Science Journal, 2011)
Rapid and accurate identification of Methicillin Resistant Staphylococcus aureus is essential in limiting the spread of this bacterium. The aim of study is the detection of Methicillin Resistant Staphylococcus aureus (MRSA) and determining their susceptibility to some antimicrobial agent. A total of fifty clinical Staphylococcus aureus, isolated from the nose of health work staff in surgery unit of Kalar general hospital and from ear of patients attended to the same hospital. The susceptibilities of isolates were determined by the disc diffusion method with oxacillin (1 ?g) and cefoxitin (30 ?g), and by the mannitol salt agar supplemented with cefoxitin (MSA-CFOX), susceptibilities of isolates to other antimicrobial agent were determined by standard disc diffusion method, Brain heart infusion (BHI) agar with vancomycin was used for detection of vancomycin resistant Staphylococcus aureus. out of fifty clinical isolates of Staphylococcus aureus 36/50(72%) considered to be MRSA according to MSA-CFOX growth and cefoxitin disc susceptibility results with critical diameter